Perancangan Sistem Inventarisasi Barang berbasis Web pada Politeknik Katolik Mangunwijaya - Priyo Wibowo; Nabila Rizqi Mahardika; Dimsa Mutiara Firstayodi; Abram Darmaputra (Lembaga Pengembangan Kinerja Dosen, 2024)
Politeknik Katolik Mangunwijaya (Polteka Mangunwijaya) is a higher education institution formed by the merger of three academies in Semarang. These three academies combined to become popular study programs among the community, offering Diploma III programs in Chemical Engineering, Pharmacy, and Health Analysis. Over time, Politeknik Katolik Mangunwijaya encountered challenges in managing inventory to support organizational effectiveness and decision-making by the structural leadership. To optimize asset management, a web-based inventory information system application was developed. The choice of the web platform was based on its compatibility with all devices. The system was built using the Rapid Application Development (RAD) method with PHP programming language, the Laravel framework, Tailwind CSS, and a MySQL database. This application primarily supports the vice director, superadmin, and program study admins in stock recording, item identification using barcodes, and detailed inventory transaction reporting. This system replaces the manual recording method, which was previously considered inefficient and prone to data loss or inaccuracies. After functional testing and user acceptance, the system has proven to operate smoothly as planned and provides an effective solution for managing inventory at Politeknik Katolik Mangunwijaya.